The psychological determinants of emotional and external eating behavior in a university student sample from Turkey - ERGÜN, SERHAT; YANARTAŞ, ÖMER; ÖZERCAN, AHMET; SAYAR, MUSTAFA KEMAL (My University, 2023)
Psychological factors and adverse childhood events at an early age have been poorly investigated in relation to risky eating behavior and obesity. The importance of this relationship grows as these behaviors are becoming public health problems. The main objective of the present study was to examine the effects of interrelated psychological factors such as childhood negative life events, symptoms of depression and anxiety, and impulsivity on eating behaviors in a university student sample in Turkey. A total of 414 undergraduate students (60.4% women) in Turkey, completed the Turkish versions of the Dutch Eating Behavior Questionnaire (DEBQ) to assess emotional eating and external eating and the CDC-Kaiser Permanent Adverse Childhood Experiences (ACE), Beck Depression Inventory (BDI), Beck Anxiety Inventory (BAI), and Barratt Impulsivity Scale-11 (BSI-11). Structural equation models (SEM) were used to evaluate whether depressive/anxiety symptoms could be a mediator between impulsivity and emotional eating/external eating. Childhood adverse events were both weakly correlated with eating behavior and impulsivity measures (r = .18,r = .275, p <.001, respectively). Depression and anxiety levels were found to be significantly associated with all variables except for the body mass index (BMI; r = .121-.395, p <.001). Body mass index (BMI) was also significantly correlated with emotional eating (r = .231, p <.001) and restrained eating (r = .226, p <.001). Impulsivity was positively and directly associated with symptoms of anxiety and depression and emotional and external eating (respectively 0 = .27, p <.001; 0 = .31, p <.001; 0 = .16, p = .006; 0 = .13, p = .047). The effect of adverse experiences on both emotional eating (0 = .147; 95% CI [.087, .247]) and external eating (0 = .091; 95% CI [.032, .168]) was found to be partially mediated by impulsivity and symptoms of anxiety and depression. The results supported the proposition that symptoms of depression and anxiety levels are mediators between impulsivity and emotional eating/ external eating. This finding suggests that a through psychological assessment should be taken into consideration when evaluating the eating behavior of university students and prevention and treatment strategies applied for disordered eating behaviors in the future.

Psihološki faktori i štetni događaji iz detinjstva (eng. Adverse childhood events) su slabo proučavani u kontekstu rizičnih prehrambenih ponašanja i gojaznosti. Važnost ove veze raste sa činjenicom da ova ponašanja postaju problem javnog zdravlja. Glavni cilj ove studije je bio da se ispita efekat povezanih psiholoških faktora kao što su štetni događaji iz detinjstva, simptomi depresije i anksioznosti i impulsivnost na prehrambena ponašanja na uzorku studenata iz Turske. Ukupno 414 studenata osnovnih studija (60,4% žena) iz Turske je popunilo tursku verziju Holandskog upitnika prehrambenih ponašanja (eng. Dutch Eating Behavior Questionnaire; DEBQ) radi procene emocionalnog i eksternog jedenja, kao i CDC-Kajzer Permanente Upitnik štetnih iskustava iz detnjstva (CDC-Kaiser Permanente Adverse Childhood Experiences; ACE), Bekov invetar depresivnosti (BDI), Bekov inventar anksioznosti (BAI), i Baratovu skalu impulsivnosti (BSI-11). Strukturalno modeliranje (SEM) je korišćeno radi procene da li depresivni/anksiozni simptomi mogu biti medijator veze između impulsivnosti i emocionalnog/ eksternog jedenja. Štetna iskustva iz detinjstva su slabo korelirala sa merama prehrambenih ponašanja i impulsivnosti (r = 0,18, r = 0,275, p < 0,001, respectively). Nivoi anksioznosti i depresivnosti su korelirali značajno sa svim varijablama sem sa indeksom telesne mase (BMI; r = 0,121 ‒ 0,395, p < .001). Indeks telesne mase (BMI) je bio značajno povezan sa emocionalnim jedenjem (r = 0,231, p < 0,001) i sa eksternim jedenjem (eng. restrained eating; r = 0,226, p < 0,001). Impulsivnost je bila pozitivno i direktno povezana sa simptomima anksioznosti i depresivnosti, kao i sa emocionalnim i eksternim jedenjem (redom: β = 0,27, p < 0,001; β = 0,31, p < 0,001; β = 0,16, p = 0,006; β = 0,13, p = 0,047). Veza štetnih iskustava iz detinjstava i emocionalnog (β = 0,147; 95% CI (0,087. 0,247)) i eksternog (β = 0,091; 95% CI (0,032, 0,168)) jedenja bila je delimično posredovana impulsivnošću i simptomima anksioznosti i depresivnosti. Rezultati su govorili u prilog tezi da su simptomi depresivnosti i nivo anksioznosti medijatori veze između impulsivnosti i emocionalnog/eksternog jedenja. Ovaj nalaz sugeriše da prilikom evaluacije prehrambenih ponašanja studenata i razmatranja strategija koje će biti primenjene za rešavanje problema neurednih prehrambenih navika, u budućnosti treba, kao opciju razmatrati i temeljnu psihološku procenu pacijenta.
Psihološke determinante emocionalnih i eksternih prehrambenih ponašanja na uzorku studenata iz Turske
Keywords: Sosyal ve Beşeri Bilimler; Psikoloji; Social Sciences and Humanities; Psychology; PSİKOLOJİ, MULTİDİSİPLİNER; Temel Bilimler (SCI); PSYCHOLOGY, MULTIDISCIPLINARY; PSYCHOLOGY; Natural Sciences (SCI); Psikoloji (çeşitli); Genel Psikoloji; Sosyal Bilimler ve Beşeri Bilimler; Psychology (miscellaneous); General Psychology; Social Sciences & Humanities; Eating behavior; obesity; childhood adverse events; depression; anxiety; impulsivity; PSYCHOMETRIC PROPERTIES; DEPRESSIVE SYMPTOMS; LIFE-STYLE; OVERWEIGHT; OBESITY; STRESS; ABUSE; QUESTIONNAIRE; IMPULSIVITY; DISORDERS; prehrambena ponašanja; gojaznost; štetna iskustva iz detinjstva; depresija; anksioznost; impulsivnost